Mixed-Integer Linear Programming Model for Production Planning: A Case Study at Sawn Timber Production - Octavia Riskadayanti; Muhammad Hisjam; Y Yuniaristanto (Jurnal Teknik Industri, 2020)
The sawmill industry is an industry that processes logs into sawn timber products through several processes to maximize profits and meet customer demand. The process involves essential operations that have to be coordinated to get the desired product with the available resources optimally. Efficient operations can be achieved through optimal production planning by considering some factors to optimize the number of sawn timber product combinations. Optimal production planning is expected to have an impact, such as reducing the use of raw materials that can affect inventory and procurement. In this research, the author has developed a mathematical model for production planning to determine the optimal number of sawn timber product combinations. Problems were solved using mixed-integer linear programming methods with mathematical modeling that aimed for maximizing profit. Production costs, raw material costs, and purchasing costs were critically considered in this mathematical modeling. The result showed that using the developed model could integrate the factors above, fulfill the demand, and increase company income.